Advances in Theoretical Calculation of Halide Perovskites for Photocatalysis - Liu, Xiaolin; Fan, Jichao; Huang, Changzhu (Frontiers in Nanotechnology, 2021)
Photocatalysis, which includes water splitting for hydrogen fuel generation, degradation of organic pollutants, and CO2 reduction using renewable solar energy, is one of the most promising solutions for environmental protection and energy conversion. Halide perovskite has recently emerged as a new promising material for photocatalytic applications. The exploration of new efficient halide perovskite-based photocatalysts and understanding of photocatalytic reaction mechanisms can be revealed using theoretical calculations. The progress and applications of first-principles atomistic modeling and simulation of halide perovskite photocatalysts, including metal halide perovskites, halide perovskite heterojunctions, and other promising perovskite derivatives, are presented in this review. Critical insights into the challenges and future research directions of photocatalysis using halide perovskites are also discussed.